Improving the Quality of Early Childhood Learning Through Group Learning Models: An Analysis in Early Childhood Education - Ani Yuhanidz; murniasih, Murniasih; Novi Hidayati (Muttaqien Publishing, Pusat Penelitian dan Pengabdian kepada Masyarakat STAI DR.KH.EZ.Muttaqien Purwakarta, 2025)
This research aims to analyze the application of the group learning model in Early Childhood Education (PAUD) through a literature study approach. The group learning model is known to have various benefits, especially in supporting the cognitive, social and emotional development of early childhood. This study uses qualitative methods by examining various literature sources such as scientific journals, books and related articles. The results of the analysis show that the group learning model is effective in improving children's cooperation, communication and self-confidence. Apart from that, this approach also creates an interactive and fun learning environment, which can motivate children to actively participate. However, the group learning model also has disadvantages, such as passive students who will be left behind, if collaboration is not effective, conflict will occur, and teacher supervision is more intensive. The successful implementation of this model depends on the competence of educators in designing appropriate activities and collaboration with parents. This study recommends strengthening training for educators to optimize the implementation of group learning models in PAUD.